ANALISIS PENGARUH CITRA MEREK DAN KESADARAN MEREK TERHADAP EKUITAS MEREK MELALUI LOYALITAS MEREK SEBAGAI VARIABEL INTERVENING - Kusuma, Ryan Anggra; Sugiarto Ph, Yohanes (Diponegoro Journal of Management, 2014)
This study aims to determine the extent of Djarum brand can build consumer confidence in the brand Djarum itself until today. For that brand equity should be achieved by a company to win a competition, especially in the cigarette industry. As we all know smoking becomes secondary needs among young people, but many young people there are who think smoking is their primary needs. This study uses quantitative methods. Data were collected by questionnaire technique. Respondents for this study is the population in the study were Djarum Super smokers with the number of respondents 100 people. Quantitative methods include the validity Â and reliability, the classic assumption test, testing hypotheses through F test, t test and the coefficient of determination (R2). The data analysis technique used is the linear regression analysis. And in this study using Sobel test to detect brand loyalty as intervening variable.The results of this study indicate that the brand image and brand awareness and a significant positive effect on brand loyalty, brand loyalty subsequently accepted as an intervening variable in mediating the brand image and brand awareness to brand equity.